Simulation of Point Defects Formation in the Fuel Element of a Nuclear Power Plant’s Wave Reactor - Opyatyuk V. V.; Kozlov I. L.; Karchev K. D.; Vistiak S. V.; Kozlov O. I.; Turmanidze R. (Журнал інженерних наук)
This paper considers the point defects that influence the operation of a wav nuclear power reactor with a uranium fuel medium. The formed individual point defects or such defect groups can produce a perturbing effect on the stability of the nuclear reactor operating mode and involve its transition to an unstable state. Studies have been carried out on the effect on the characteristics of the nuclear burnup wave in a medium with neutron multiplication for 2D geometry. For the calculation, the uranium-thorium fissile medium has been considered. The parametric calculations were carried out with 235 U different enrichment percents and different values of neutron activation energy. At that, it was assumed that the wave (flow) reactor stable operation region is located in the range of activation energies from 10–3 eV to 1 eV or in the region from 2 MeV to 8 MeV. When calculating the neutron flux intensity in a wave reactor, the influence of point defects and their aggregates on the decelerating elastically scattered neutrons’ flux density and the flux density of decelerating non-elastically scattered neutrons was considered. The dependences of the point defects formation rate on the medium fissile temperature for several compositions of the uranium-thorium medium are obtained. As visually identified, the graphic materials obtained during the calculations are similar to the photos of fuel rods after the energy campaign.